2023
DOI: 10.1002/jimd.12649
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for aromatic L‐amino acid decarboxylase deficiency: Requirements for safe application and knowledge‐generating follow‐up

Agathe Roubertie,
Thomas Opladen,
Heiko Brennenstuhl
et al.

Abstract: The autosomal recessive defect of aromatic L‐amino acid decarboxylase (AADC) leads to a severe neurological disorder with manifestation in infancy due to a pronounced, combined deficiency of dopamine, serotonin and catecholamines. The success of conventional drug treatment is very limited, especially in patients with a severe phenotype. The development of an intracerebral AAV2‐based gene delivery targeting the putamen or substantia nigra started more than 10 years ago. Recently, the putaminally‐delivered const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The disease is more prevalent in the Asian population, likely due to a founder effect of a specific mutation [2]. In addition, preliminary results from newborn screening studies in central Europe confirmed the former estimated prevalence of 1-2 in around 500.000 newborns [6].…”
Section: Introductionmentioning
confidence: 65%
“…The disease is more prevalent in the Asian population, likely due to a founder effect of a specific mutation [2]. In addition, preliminary results from newborn screening studies in central Europe confirmed the former estimated prevalence of 1-2 in around 500.000 newborns [6].…”
Section: Introductionmentioning
confidence: 65%
“…Upstaza (eladocagene exuparvovec) was recently approved in the European Union and is the first therapy to treat AADC deficiency. 28 29 With the introduction of gene therapy for AADC deficiency and a potential for alleviating symptoms and modifying the natural progression of the disorder, it becomes even more crucial to recognize and accurately establish an early diagnosis. Consensus guidelines have been brought out in a recently published document that will serve to provide further guidance in managing this challenging condition.…”
Section: Discussionmentioning
confidence: 99%
“…Over time, it would be of utmost patient benefit to have an international, standardised approach from pre‐screening to post‐gene therapy surveillance, using appropriate disease‐specific registries, to consolidate clinical data, allowing for thorough treatment evaluations, especially in rare diseases like IEM‐NT. 159 …”
Section: Discussionmentioning
confidence: 99%